Regulation of entry and pricing in truck transportation - MacAvoy, Paul W.; Snow, John W. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1977)
This volume provides one set of the analytical studies on regulatory reform that were still in process at the end of 1976. It provide an insight into the major issues I the debate over trucking deregulation.
Ford Administration papers on regulatory reform.
Includes bibliographical references.
osa 22/01/2019
Loans
Keywords: Trucking; Industrial policy